2023
DOI: 10.1530/eor-22-0118
|View full text |Cite
|
Sign up to set email alerts
|

How to treat stiffness after proximal humeral fractures?

Abstract: Shoulder stiffness is a frequent complication after proximal humeral fractures treated with or without surgery. Shoulder stiffness is associated with high rates of absence from work and a significant financial burden for the healthcare system. Secondary stiffness is characterized by additional extracapsular adhesions, including subacromial, subcoracoid, and subdeltoid spaces, usually derived from post-fracture or post-surgical extraarticular hematomas. Several secondary causes may coexist with capsular and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
(77 reference statements)
1
3
0
Order By: Relevance
“…This finding highlights the ability of the intramedullary PMMA strut to provide additional support within the medullary canal, thus decreasing the load on the locked screw and minimising the risk of humeral head varus and screw cut-out. Our results are consistent with previous biomechanical studies and support the potential clinical benefits of using PMMA struts in this context [17][18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding highlights the ability of the intramedullary PMMA strut to provide additional support within the medullary canal, thus decreasing the load on the locked screw and minimising the risk of humeral head varus and screw cut-out. Our results are consistent with previous biomechanical studies and support the potential clinical benefits of using PMMA struts in this context [17][18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 92%
“…Few clinical reports exist on the results of locking plate fixation of proximal humeral fractures, and short-term functional outcomes and complications, such as humeral head varus collapse or intra-articular screw penetration have been variable in patients with osteoporosis [7][8][9]. In vitro studies indicated that these complications arise from locking plates without medial column support [10][11][12][13][14][15][16][17]. Biomechanical studies show that locking plates with intramedullary fibular allograft fixation can enhance the stability of the construct and reduce the humeral head migration compared to locking plate fixation alone [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…A review was conducted in PubMed, Embase, and Scopus databases to identify relevant studies reporting complication rates in surgically managed greater tuberosity fractures [2,[43][44][45][46][47][48][49][50][51][52]. Outcomes were variable between series, with heterogeneous reports and data, and limited studies with high level of evidence were obtained.…”
Section: Complicationsmentioning
confidence: 99%
“…Shoulder stiffness is a frequent complication after proximal humeral fractures treated with surgery. [ 9 ] Accordingly, it is crucial to prevent shoulder stiffness in the treatment of proximal humeral fractures. Currently, there is no consensus on the diagnostic criteria for shoulder stiffness, which is often diagnosed based on limited active and passive movement of the shoulder, including forward flexion, lateral rotation, and posterior internal rotation.…”
Section: Introductionmentioning
confidence: 99%